Implementation of Progressive Legal Theory in Law Enforcement in Indonesia - Siti Romlah; Salma Zavira; Khansa Muafa (Journal La Sociale, 2020)
The aim of this research is to analyze progressive legal theory in law enforcement in Indonesia. This research used a normative research method by examining library materials regarding the Implementation of Progressive Legal Theory in Law Enforcement in Indonesia. The approach in this research was a statute approach and a conceptual approach. Normative research used 2 types of legal materials, namely primary and secondary legal materials. The technique of collecting legal materials in this research used written techniques or commonly referred to as library research. Legal materials analyzed using the Conceptual Analyzer. The research result obtained was a fundamental ideology in Progressive Legal Theory according to Prof. Sadjipto Raharjo is achieving broad justice for society. When the justice produced by positive law only produces benefits for certain individuals and groups, law enforcement officials are required to think philosophically to carry out liberations in knowledge, theorizing, and practice. Thus it can be concluded that in the implementation of Progressive Legal Theory in Indonesia, it would be wise to start with the development of the rule of law. Progressive legal also has similarities with sociological jurisprudence in terms of focus on legal studies which do not only see law as written rules.